THE EFFECTIVENESS OF TEAMS GAMES TOURNAMENT (TGT) LEARNING MODEL TOWARD STUDENTS MATHEMATICS LEARNING OUTCOMES OF CLASS VIII AT SMP N 2 TEMPEL SLEMAN REGENCY - Fifi Ninawati; Suparman Suparman (Universitas Ahmad Dahlan, 2017)
The research is done based on the observation that the learning process is still focused on teacher-centered so that students are less active in the learning process and the result is low. The objective of the study is to know the effectiveness of the Teams Games Tournament with a live learning model toward student's mathematics learning outcomes of class VIII at SMP N 2 Tempel sleman regency of odd semester in academic year 2016/2017. This research uses postest-only design. The population of this research is the student of class VIII SMP Negeri 2 Tempel academic year of 2016/2017, which consists of 157 students which is divided into five classes. The sample is taken by 2 classes with a random sampling technique using a lottery, it is delivered by class VIII D as an experiment class and class VIII B as the control class. The collecting data technique uses test. The instrument of collecting data uses the student’s study result. The instrument test of collecting data uses validity, distinguishing capacity and reliability test. The technique of data analysis includes a normal test, homogeny test, then hypothesis test t. The result of the study on significant level α = 5% with df = 59 shows that: (1) there are some differences in the result of Mathematic study between the student which use learning model Teams Games Tournament than the student which use live learning model. It can be seen that = 2,6332 and = 2,00134 get . (2) mathematic learning uses learning model Teams Games Tournament is more effective than a live learning model toward the result of Mathematic learning. The result shows that = 2,6332 and = 1,6713 get .